Analisis faktor-faktor yang mempengaruhi permintaan uang di provinsi Bali menggunakan pendekatan error correction model (ECM) - Sitohang, Gresia Septina; Suharianto, Joko; Silfani, Dwi; Manihuruk, Frido Evindey; Oktania, Ainur; Sari, Arsiska; Irsyad, Ferozi Ramdana (Jurnal Pendidikan Ekonomi (JUPE), 2025)
Demand for money is an important indicator in the economy that reflects the needs of the public and economic actors for cash and non-cash money for transactions, investments, and reserves. Bali Province, as one of the main tourist destinations in Indonesia, has unique and interesting economic dynamics to study, especially in terms of money demand. Over the period 2000-2023, changes in the demand for money in Bali Province were influenced by various macroeconomic factors such as inflation, interest rates, and Gross Domestic Product (GDP). This study aims to analyze the factors that influence the demand for money in Bali Province by using the Domowitz-El Badawi Error Corection Model (ECM) on secondary data obtained from the Bali Central Bureau of Statistics. The result revealed 24.4% of the imbalance from the previous period will be adjusted in the current period. This negative and significant coefficient indicates that the ECM model used is valid. In the long run, inflation and GDP have a positive effect on money demand, while interest rates have a negative effect. In the short term, inflation has a positive effect, while the BI rate has a negative effect on money demand. However, GDP shows a negative coefficient, which may indicate the influence of other factors in the short term.